Deteksi Awal Kandungan Logam Tembaga (Cu) pada Tanaman Kangkung Darat (Ipomoea reptans) - Andi Badli Rompegading; Nur Fadhillah Muhlis; Rizky Arfadilla; Nur Indah Sari; Ayu Muliana; Rahmawati Rahmawati; Mutmainnah Gani; Ahmad Rinaldy; Muh. Faqhi S.; Mirjawanda Mirjawanda; Zakiah Tantu; Aisyah Gusfira; Uswah Trywulan Syah; Rizal Irfandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the initial content of copper metal found in land kangkung (Ipomoea reptans) plants. The method used is the descriptive quantitative analysis method. The results showed that samples 1, 2, 3, and 4 each had <0.50 mg/kg copper metal found in land kangkung. In conclusion, land kangkung has not been polluted, so it is safe for consumption and can also be used as phytoremediation in an environment contaminated by heavy metals. Keywords: Detection, Kangkung Land (Ipomoea reptans), Copper Metal (Cu)